Assessment of trace elements concentration in cosmetic foundation using X-ray fluorescence technique - Camila Sampaio Nogueira; Rodrigo Sanas Zamboni; Sergei Anatolyevich Paschuk; Janine Nicolosi Correa (Brazilian Journal of Radiation Sciences)
Facial foundations play a significant role in beauty routines. However, the presence of heavy metals and toxic elements in cosmetics is a concern due to potential health risks. This study investigated the chemical composition of 52 facial foundation samples obtained in Curitiba and São Paulo, Brazil, using X-ray fluorescence for elemental identification. Quantification was performed using the standard addition method and calibration curves. The results indicated the presence of Cu, Zn, Br, Zr, and Ba in concentrations exceeding the limits established by the Brazilian Health Regulatory Agency (ANVISA). Cd and Ni, elements prohibited in cosmetic formulations, exhibited maximum concentrations of 277 ± 51 µg/g and 130 ± 10 µg/g, respectively. The highest concentration of Zr reached 589 ± 57 µg/g, approximately six times the regulatory limit. In contrast, Ba concentrations exceeded 14,000 µg/g, approximately 60 times the limit, with the highest concentration recorded at 30,867 ± 1,500 µg/g. These findings underscore the need for rigorous monitoring of cosmetic products in Brazil and highlight discrepancies between the marketed cosmetics and ANVISA regulations. Additionally, this study contributes to the growing knowledge regarding potentially harmful elements in facial foundations.